STUDI SIFAT MAGNETIK DAN UKURAN PARTIKEL ABU VULKANIK ERUPSI GUNUNG SINABUNG KABUPATEN KARO MENGGUNAKAN PROBE PASCO 2162 - Salomo Salomo; Serima Apriani Purba; Riad Syech (Komunikasi Fisika Indonesia, 2018)
This study aims to determine the magnetic properties and particle size of the volcanic ash of Sinabung Mount with experiment method. Magnetic properties studied were magnetic degree, magnetic induction magnetic susceptibility, and mass susceptibility of sample. The samples used were volcanic ash taken from the west part of Sinabung, precisely at Gurukinayan village. The ash samples were taken horizontally on the slopes of the Mountain with the amount of 1.5 Kg each point with the number of 10 points (A to J). Separation of concentrate of ash was done using a Neodymium Iron Boron (NdFeB). The magnetic induction of ash and concentrate was measured using a Pasco 2162 Probe using a solenoid is 3 cm in diameter, 10 cm in length and 2000 coil turns. Magnetic induction without a core was measured as a current function (2,4,6,8,10)A and a distance of 1 to 5 mm. The total magnetic induction of ash and concentrate was measured as a current function and the particle sizes was measured using a Light Microscope. The results showed that the greate magnetic degree value at point B of 7.02% and the lowerst level of magnetism is at point J was 1.07%. The largest particle sizes is at point B and the smallest is at point J with particle size of 0.175-0.90 mm. The highest average magnetic susceptibility value for concentrate at point B is 87.32 x 10-3 and the lowest at point F is 20 x 10-3. Based on the mass susceptibility value of the concentrate obtained the volcanic ash of Mount Sinabung is at interval (46–80.000) x 10-8 m3/kg of mass susceptibility value at each location point which contains Ilmenite particles (FeTiO3).